Storm born ebook - Mead, Richelle (Dark Swan, 2008)
A spirit hunter is the target of deadly danger and Otherworldly lust in a paranormal thriller by the New York Times bestselling author of Vampire Academy . Eugenie Markham is a powerful shaman who does a brisk trade banishing spirits and fey who cross into the mortal world. Call her a mercenary if you want, but it's just business to her. Until now. Hired to find a teenager who's been taken to the Otherworld, Eugenie encounters a startling prophecy—one that uncovers dark secrets about her past and claims that her first-born will threaten the future of the world. Now Eugenie is a hot target for every ambitious demon in the Otherworld, and the ones who don't want to knock her up want her dead. Eugenie handles a Glock as smoothly as she wields a wand, but she needs some formidable allies for a job like this. She finds them in Dorian, a seductive fairy king with a taste for bondage, and Kiyo, a gorgeous shape-shifter who redefines animal attraction. But with enemies growing bolder and time running out, the greatest danger is yet to come, and it lies in the dark powers that are stirring to life within Eugenie herself. "Storm Born is my kind of book — great characters, dark worlds, and just the right touch of humor. A great read." —Patricia Briggs